THE SYNTHESIS OF 1,3-DIMETHYL-6,7-DIMETHOXY-3,4-DIHYDROISOQUINOLINE FROM METHYLEUGENOL : APPLICATION OF RITTER REACTION FOR DIRECTLY CYCLIZATION - M. Farid Rahman; Elvina Dhiaul Iftitah (Indonesian Journal of Chemistry, 2006)
The synthesis of 1,3-dimethyl-6,7-dimethoxy-3,4-dihydroisoquinoline from methyleugenol with application of Ritter reaction for directly cyclization was presented. This research was carried out in 2 steps : (1) Determination of intermediate stability that undergo in the reaction by using hyperchem version 6 with AM 1 semi empirical method, and (2) Synthesis of dihydroisoquinoline from methyleugenol and acetonitrile with acid catalyst (H2SO4) in the laboratory. The result of AM 1 calculation found that generally, the intermediate encourage the formation dihydroisoquinoline product, had low energy were compared with the intermediate in other product. Therefore, the dihydroisoquinoline product was easily formed. The result of experimental laboratory found that dihydroisoquinoline could be synthesed from methyleugenol and acetonitrile in the presence sulphuric acid under reflux in 74,92% yields. In despite, the minor product was formed with amount 6,74%. While the reaction at room temperature gave dihydroisoquinoline in poor yield about 11,42%.